MANAJEMEN SUMBER DAYA MANUSIA BERBASIS KOMPETISI DI SMA AL MUTTAQIN KOTA TASIKMALAYA - Adun Rahman; Diansyah Permana; Mohamad Erihadiana; Gilang Muhamad Fajri Faresi; Fahad Abdusomad (LP2M IAIN Sultan Amai Gorontalo, 2025)
The development of Islamic educational institutions is currently quite rapid and has become a favorite choice for the community. This is inseparable from the success of managing human resources (HR). This study aims to examine competition-based HR management at Al Muttaqin High School in Tasikmalaya City, an educational institution that is superior in terms of achievement compared to other schools. The focus of the study includes basic concepts, strategies, implementation, benefits, objectives, and challenges in HR management, using best practices at the institution as a case study. Douglas McGregor's theory is the basis for this study. This study uses a qualitative method with in-depth interviews and observations of the academic community at Al Muttaqin High School. The research findings identify several basic concepts of competition-based HR management, including (1) Quality education, which includes teaching, curriculum innovation, organization, learning culture, educational technology, diversity, and leadership. (2) Strategy and implementation, such as learning vision, learning culture, learning investment, and achieving vision targets. (3) Benefits and objectives, including increasing individual motivation, team collaboration, innovation, operational efficiency, and parent and student satisfaction. (4) Best practices at the institution include (a) Performance assessment. (b) Project-based assessment. (c) Innovation competition. (4) Student feedback. The implications of this research show that this approach is able to increase work enthusiasm and encourage HR progress at Al Muttaqin High School, Tasikmalaya City.